Characterization of inflorescence-predominant chitinase gene in Metroxylon sagu via differential display - Hairul Azman, Roslan; Syahrul Bariyah, Anji (Springer, 2011)
Chitinase is an enzyme that catalyzes the degradation of chitin, commonly induced upon the attack of pathogens and other stresses. A cDNA (MsChi1) was isolated from Metroxylon sagu and expressed predominantly in the inflorescence tissue of M. sagu, suggesting its role in developmental processes. The chitinase cDNA was detected and isolated via differential display and rapid amplification of cDNA ends (RACE). Primers specific to M. saguchitinase were used as probes to amplify the 3′-end and 5′-end regions of chitinase cDNA. Transcript analysis showed that chitinase is expressed in inflorescence and meristem tissues but was not detected in the leaf tissue. Sequence analysis of amplified cDNA fragments of 3′-end and 5′-end regions indicated that the chitinase cDNA was successfully amplified. The M. saguchitinase cDNA isolated was approximately 1,143 bp long and corresponds to 312 predicted amino acids. Alignments of nucleotide and amino acid have grouped this chitinase to family 19 class I chitinase.